Kajian Exclusive Dealing dan Pengaruhnya terhadap Tingkat Persaingan Usaha dan Iklim Bisnis pada Rantai Pasok Industri Komponen - Laraswati, Levinia Dian; Sutopo, Wahyudi; Yuniaristanto, Yuniaristanto (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
Supply chain of vehicle industry is one of the supply chain that involves many entities. The high number of entities make the creation of a business network to improve the effectiveness and efficiency of business activities better known as vertical integration. However, the creation of excessive vertical integration and not pay attention to the rules of fair competition can also have a negative impact on the business climate conditions. Component industry as part of the car industry in the downstream sector has shown the existence of an indication of a exclusive dealing with their customers. The research conducted an analysis using structural equation modeling to know abaout the relationship between exclusive dealing indication the level of competition and the business climate in Indonesia component industry. And based on the processing and analysis of data, it can be concluded that there is a relationship between the indication of exclusive dealing with the level of competition and business climate of the industry.